A Student’s Guide to Landscape Architecture - Suriati Ahmad (Penerbit UTHM, 2023)
A Student’s Guide to Landscape Architecture is an academic coursebook produced by the Programme of Landscape Architecture, Universiti Teknologi MARA Perak Branch, aiming to provide additional reference material to the student while supporting the running of the current sylabus. My deepest gratitude to Allah for His guidance and blessing, where all teh hard work and efforts finally come to an end after two years of planning. The unique features aded to this book are the illustration and detailed manual sketches and render drawn by the academic members of this programme. This effort depicts the seriousness of this coursebook that can be a good source of reference, guided reading material and extended excercise handout, especially for students, designers, and other potential readers who keen to understand knowledge related to landscape architecture. Fice chapter were designed for this coursebook, encompassing important landscape architecture strand that focuses on landscape design principles, landscape design process, landscape construction, landscape sciences and landscape planting.